Digital Twins and the Stendhal Syndrome - Franco Niccolucci; Achille Felicetti (Computers)
The “Stendhal Syndrome” mentioned in the title refers to the first (early 19th century) documented perception of the role of intangible aspects in characterising cultural heritage. This paper addresses the semantic organisation of data concerning the digital documentation of cultural heritage, considering its intangible dimension in the framework of Digital Twins. The intangible component was one of the aspects motivating the need of setting up the Heritage Digital Twin (HDT) ontology and its extensions, published in a series of papers since early 2023. In this paper, we analyse how places, persons, and things may give value to a heritage asset, being linked to and supporting its intrinsic cultural significance. This development stems from the consideration of heritage studies and research carried out by scholars and organisations such as UNESCO and ICOMOS, which underline the paramount role of the intangible component in defining heritage assets. The paper then expands the previous semantic structure of the Heritage Digital Twin ontology as concerns the intangible aspects of a heritage asset, extending the HDT concepts by defining new classes and properties related to its intangible component. These are discussed in various cases concerning places, monuments, objects, and persons, and fully developed in examples.